The Effect of Productive Zakat, Business Experience, and Mentoring on Farmers’ Revenues (Survey on Lumbung Desa Program by Sinergi Foundation in Cibaeud Village, Cigalontang District, Tasikmalaya Regency) - Irfaany Fauziyah Taufiq; Kusnendi .; Aas Nurasyiah (International Journal of Zakat, 2018)
This study aims to determine the effect of productive zakat, business experience and mentoring on the income of farmers participating in the Lumbung Desa-Sinergi Foundation program in Cibaeud Village, Cigalontang District, Tasikmalaya Regency. The research method used is an explanatory survey with a questionnaire as the data collection tool. The sampling technique is saturated sampling twith 68 respondents. Linear regression analysis is used as the data analysis technique. The results show that productive zakat and business experience have a positive and significant effect on farmers' income, while the assistance has a positive but not significant effect.